PEGARUH MOTIVASI KERJA, KEPEMIMPINAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (STUDI PADA PEGAWAI KECAMATAN MUARA JAWA, KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR) - Irfan Febriansyah; Abd Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT“This study aims to test and analyze the Effect of Work Motivation, Work Leadership and Job Satisfaction on Employee Performance in Muara Java District Office. Kutai Kartanegara, East Kalimantan both partially and simultaneously. In this study the population amounted to 39 employees and all were taken as samples. Data collection through questionnaires, data analysis in this study using SPSS version 22. The sampling technique uses quantitative methods, while the data testing techniques used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis”. The results of the analysis show that partially work motivation and work leadership are not significant towards the performance of the staff of the Muara Jawa District Office, while the simultaneous analysis of Work Motivation, Work Leadership and Job Satisfaction has a positive and significant effect on the Employee Performance of the Muara Jawa District Office, Kab. Kutai Kartanegara, East Kalimantan. Keywords: Work Motivation, Work Leadership, Job Job Satisfaction and Employee Performance